Effects of Slaughter Age on Myosin Heavy Chain Isoforms, Muscle Fibers, Fatty Acids, and Meat Quality in Longissimus Thoracis Muscle of Tibetan Sheep - Bao, Gaoliang; Liu, Xiu; Wang, Jiqing; Hu, Jiang; Shi, Bingang; Li, Shaobin; Luo, Yuzhu (Frontiers in Veterinary Science, 2021)
Tibetan sheep is one of the dominant livestock at Qinghai-Tibet Plateau, which is the main food source of local people. In order to investigate the effect of slaughter age on meat quality, fatty acid profile and expression of myosin heavy chain (MyHC) isoform genes were analyzed in Tibetan sheep. A total of 24 Tibetan sheep including 4 months old (4 m), 1.5 years old (1.5 y), 3.5 years old (3.5 y), and 6 years old (6 y) were randomly selected. The results indicated that the MyHC IIx and MyHC IIb mRNAs increased with age, whereas MyHC IIa mRNA decreased. MyHC I mRNA was highest at 3.5 y. There were differences in the muscle fiber types of Tibetan sheep at different ages. Intramuscular fat (IMF) was highest at 1.5 y, the pH45min and pH24h value of 6 y sheep were lower than the other groups, the shear force increased with age (p < 0.05), and drip loss increased with age (p < 0.01). Tibetan sheep at 1.5 y had lower saturated fatty acid (SFA) contents and higher monounsaturated fatty acid (MUFA) contents (p < 0.05). Different muscle fiber types influence the meat quality and fatty acid composition of Tibetan sheep with increasing age. These results demonstrated the effect of age on meat quality of Tibetan sheep through regulation of expression of the MyHC isoforms which changed the myofiber types, and 1.5 y Tibetan sheep meat was more suitable for a healthy human diet.